BIRDS DISTRIBUTION IN PT EKOSISTEM KHATULISTIWA LESTARI, KUBU RAYA REGENCY, WEST KALIMANTAN PROVINCE - Iqbal Nur Ardiansyah; Nirmala Ayu Aryanti; Hari Ahmadi (Department of Forest Resources Conservation and Ecotourism - IPB University, 2020)
IUPHHK-RE PT Ekosistem Khatulistiwa Lestari is the habitat of various wildlife species, comprises of a restoration forest area surrounded by production forest and oil palm plantations. The threats of damages from illegal logging and land clearing activities tend to threaten the wildlife existence. Therefore, this study aims to determine the distribution and diversity of bird species in PT Ekosistem Khatulistiwa Lestari. The study was conducted from January - February 2019, and data collection was conducted using the IPA (Index Ponctualle deAbondance) method. Furthermore, data analysis used diversity index, evenness index, and species similarity with dendrogram analysis using SPSS 21. The results showed that the highest bird species were found in mangroves (32 species), old swamp scrubs (26 species), young swamp scrubs (24 species), plantations (13 species), and settlement (15 species) habitats. Meanwhile, the diversity index of bird species in the five habitat types is classified as medium diversity. Species evenness with the highest value is settlement (E = 0.93). The dendrogram image of the settlement area showed bird species, which can be found in the other four habitats. Keywords: diversity, bird distribution, West Borneo, dendrogram